Efficiency Wages : Models of Unemployment, Layoffs, and Wage Dispersion - Weiss, Andrew (Book collections on Project MUSE., 2014)
Known for his seminal work in efficiency-wage theory, Andrew Weiss surveys recent research in the field and presents new results. He shows how wage schedules affect the kinds of workers a firm employs and how well those workers perform on the job. Using straightforward examples, he demonstrates how efficiency-wage theory can explain labor market outcomes and guide government policy. There is a separate section of applications to less developed countries. ""Efficiency-wage models represent one of the most important developments in economic theory of recent years. They have, at last, provided